Evaluation of a new e-learning framework for teaching nuclear medicine and radiology to undergraduate medical students. (July 2019) - Gulati, Ankush; Schwarzlmüller, Thomas; du Plessis, Elsa; Søfteland, Eirik; Gray, Robert; Biermann, Martin
Background: Radiology and nuclear medicine have traditionally been taught in a series of lectures and seminars concluded by an examination testing knowledge rather than skills. Purpose: To emphasize skills in the students' learning process, we developed and evaluated a new e-learning framework for teaching medical imaging. Material and Methods: The framework consists of electronic lectures, a learning management system (LMS), and a diagnostic viewing system. Students were to review positron emission tomography/computed tomography (PET/CT) examinations of five cases of lung cancer. The framework was evaluated in an objective structured clinical examination (OSCE) taken by 139 undergraduate students at the end of their third year, and in a comparative survey of two groups of 85 and 84 students in the fifth and sixth year who were taught the same oncology course with and without mandatory PET/CT exercises, respectively. Results: Of the 139 third-year students, 134 (96%) passed the OSCE PET/CT station according to the predefined criteria. While 85/85 (100%) of the fifth-year students had taken exercises when they were mandatory, only 2/84 (2%) of the sixth-year students had reviewed the cases on a voluntary basis ( P < 0.001). Of the 25 survey responders in the fifth year, 24 (96%) agreed that the mandatory PET/CT exercises had promoted their learning while the sixth-year students, whose course concluded with a multiple-choice examination, emphasized the utility of online lectures. Conclusion: The new e-learning framework teaches students basic competency in PET/CT navigation and interpretation and is associated with a high degree of student satisfaction.